(untitled) (Journal of Comparative & International Higher Education, 2022)
I am pleased to share Volume 14, Issue 2, 2022 of the Journal of Comparative and International Higher Education (JCIHE). In this current issue JCIHE is honored to publish articles of higher education on the following countries: Azerbaijan, Barbados, Canada, China, Hungary, Iraq, Tajikistan, Taiwan, United Kingdom, and United States. JCIHE publishes new and emerging topics in comparative and international higher educational whose themes represent scholarship from authors from around the world. Two broad themes are represented in the articles in the 14(2) Issue: Student Learning Strategies and Institutional Context. For this issue, the Editorial Board invited two high-profile internationalists: Allan Goodman, of the Institute of International Education and Mirka Martel of the Institute of International Education to write a reflective essay about the effects of COVID-19, on student mobility. They focus on changes between the different waves of COVID-19 and projections for the future. We conclude this issue with a Book Review by Sneha Bhasin.